2000
DOI: 10.1211/146080800128735926
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Activity of Fluorinated Derivatives of Sulindac Sulphide and Sulindac Sulphone

Abstract: The synthesis of fluorinated derivatives of the sulphide and sulphone metabolites of sulindac, a non‐steroidal anti‐inflammatory agent with chemopreventative activity, is reported. The key step in the synthesis is a Pummerer‐rearrangement of the parent sulindac sulphoxide using (diethylamino)sulphur trifluoride as an activating agent and as a source of the fluoride nucleophile. The reaction leads to the formation of the 4‐fluoromethylthio and 4‐fluoromethylsulphonyl derivatives of sulindac (4a and 4b, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The acids could be esterified with alcohols under acidic conditions and hydrolyzed with LiOH. 55 Hydrolysis was not observed for compounds derived from 10c and 10d . The ester products either crystallized from the reaction mixture or were extracted and purified by chromatography.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The acids could be esterified with alcohols under acidic conditions and hydrolyzed with LiOH. 55 Hydrolysis was not observed for compounds derived from 10c and 10d . The ester products either crystallized from the reaction mixture or were extracted and purified by chromatography.…”
Section: Resultsmentioning
confidence: 97%
“… 50 53 Recent reports have indicated that the benzylidene-indene acetic acid derivative 1b can be structurally re-engineered to improve isoform-specific COX binding inter alia. 43 , 54 , 55 In the present study, compound 2 , the E -2′- des -methyl-sulindac sulfide [( E )-DMSS] analogue of 1b , served as the lead scaffold for construction of potential COX-1-selective inhibitors. Modifications were made at the carboxyl, benzylidene, and 5′-position of the indene ring (Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Considerations of the toxicity resulting from non‐selective COX inhibition (suppression of prostaglandin synthesis) and the different responses of COXs to SLDs suggest that an SLD derivative with the high in vitro AR inhibitory activity of SLD but without COX inhibition could be more promising for diabetic or other AR related medical therapies. Derivatives of SLD sulfone have been synthesized as antineoplastic agents with little or no inhibition of COXs activity [23,24], but the AR inhibition mechanism of SLD at the molecular level remains unknown, and it is unclear whether the metabolites are responsible for the inhibition of AR by SLD.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the strategic fluorine-containing substituents, the monofluoromethylthio group is widely used by the pharmaceutical industry in many drugs and drug candidates. Well-known examples include antiflammatory drug Androstanes and Fluticasone, nonsteroidal antiflammatory agent fluoro-analogues of Sulindac, and cathepsin K inhibitors (Figure ). …”
mentioning
confidence: 99%